APC mutations are common in adenomas but infrequent in adenocarcinomas of the non-ampullary duodenum - Ishizu, Kenichi; Hashimoto, Taiki; Naka, Tomoaki; Yatabe, Yasushi; Kojima, Motohiro; Kuwata, Takeshi; Nonaka, Satoru; Oda, Ichiro; Esaki, Minoru; Kudo, Masashi; Gotohda, Naoto; Yoshida, Teruhiko; et al. (Journal of gastroenterology, 2021)
Background Recent studies highlighted the clinicopathological heterogeneity of non-ampullary duodenal adenomas and adenocarcinomas, but the detailed process of the malignant transformation remains unclear. Methods We analyzed 144 adenomas and 54 adenocarcinomas of the non-ampullary duodenum for immunohistochemical phenotypes, genetic alterations, and mismatch repair (MMR) status to probe their histogenetic relationship. Results The median ages of patients with adenoma and adenocarcinoma were the same (66 years). Adenomas were histologically classified as intestinal-type adenoma ( n = 124), pyloric gland adenoma (PGA, n = 10), gastric-type adenoma, not otherwise specified ( n = 9), and foveolar-type adenoma ( n = 1). Protein-truncating APC mutations were highly frequent in adenomas (85%), with the highest prevalence in intestinal-type adenomas (89%), but rare in adenocarcinomas (9%; P = 2.1 × 10 –23 ). Close associations between phenotypic marker expression and genetic alterations were observed in adenomas, but not in adenocarcinomas, excluding the common association between GNAS mutations and MUC5AC expression. MMR deficiency was more frequent in adenocarcinomas (20%) than in adenomas (1%; P = 2.6 × 10 –6 ). One MMR-deficient adenoma and three MMR-deficient adenocarcinomas occurred in patients with Lynch syndrome. Additionally, three other patients with an MMR-deficient adenocarcinoma fulfilled the revised Bethesda criteria. Conclusion The discrepant APC mutation frequency between adenomas and adenocarcinomas suggests that APC -mutated adenomas, which constitute the large majority of non-ampullary duodenal adenomas, are less prone to malignant transformation. Non-ampullary duodenal adenocarcinomas frequently exhibit MMR deficiency and should be subject to MMR testing to determine appropriate clinical management, including the identification of patients with Lynch syndrome.